Rapid Structural Analysis of a Synthetic Non-canonical Amino Acid by Microcrystal Electron Diffraction - Gleason, Patrick R.; Nannenga, Brent L.; Mills, Jeremy H. (Frontiers in Molecular Biosciences, 2021)
Structural characterization of small molecules is a crucial component of organic synthesis. In this work, we applied microcrystal electron diffraction (MicroED) to analyze the structure of the product of an enzymatic reaction that was intended to produce the unnatural amino acid 2,4-dihydroxyphenylalanine (24DHF). Characterization of our isolated product with nuclear magnetic resonance spectroscopy (NMR) and mass spectrometry (MS) suggested that an isomer of 24DHF had been formed. Microcrystals present in the isolated product were then used to determine its structure to 0.62 Å resolution, which confirmed its identity as 2‐amino‐2‐(2,4‐dihydroxyphenyl)propanoic acid (24DHPA). Moreover, the MicroED structural model indicated that both enantiomeric forms of 24DHPA were present in the asymmetric unit. Notably, the entire structure determination process including setup, data collection, and refinement was completed in approximately one hour. The MicroED data not only bolstered previous results obtained using NMR and MS but also immediately provided information about the stereoisomers present in the product, which is difficult to achieve using NMR and MS alone. Our results therefore demonstrate that MicroED methods can provide useful structural information on timescales that are similar to many commonly used analytical methods and can be added to the existing suite of small molecule structure determination tools in future studies.